Answer:
y - 1 = -2(x + 2)
Explanation:
The general structure of an equation in point-slope form is:
y - y₁ = m(x - x₁)
In this form, "x" and "y" stand for the values of one point and "x₁" and "y₁" stand for the values of another point. The variable "m" represents the value of the slope. You have been given the values of one point and the slope. When you plug them into the general form, you get this answer:
Point: (-2, 1)
m = -2
y - y₁ = m(x - x₁) <----- Point-slope form
y - y₁ = -2(x - x₁) <----- Plug -2 in "m"
y - 1 = -2(x - (-2)) <----- Plug in values from point
y - 1 = -2(x + 2) <----- Simplify